Correlation of Serum Fibroblast Growth Factor 23 With Left Ventricular Diastolic Function in Chronic Kidney Patients - Harun Harnavi; Febrianti Ika Kurnia; Kam Alexander (Green Publisher Indonesia, 2022)
Chronic Kidney Disease (CKD) is one of most common world’s health problems with constantly increasing prevalence and many complications, and cardiovascular is one of them. The earliest cardiovascular damage that can be seen is left ventricular diastolic dysfunction. In patients with CKD, there will be mineral metabolism disorders, including phosphate. Persistently increased phosphate in CKD will cause rising in Fibroblast Growth Factor 23 (FGF23) that regulates phosphate in the circulation. High level of FGF23 will directly damage the heart and stimulates cardiac remodeling that will result in cardiomyocyte damage, atherosclerosis and intramyocardial cells fibrosis. This will cause myocardial stiffness and diastolic dysfunction. The purpose of the study is to discover correlation between Fibroblast Growth Factor 23 (FGF23) serum and left ventricle diastolic function in patients with chronic kidney disease. This is an observational study with cross-sectional methods. The sample is 30 patients diagnosed with chronic kidney disease (CKD). Patients are evaluated for Fibroblast Growth Factor 23 (FGF23) level in their serum, assessed the left ventricle diastolic function by measuring early diastolic velocity of the left ventricle (lateral e’) using echocardiography.There is significantly increased of FGF23 serum levels and decreased of lateral e’ value in chronic kidney disease case. There’s also a strong correlation between FGF23 serum and filtration glomerulus rate (LFG) (p<0.05), and a strong correlation between FGF23 serum level with lateral e’ as a component of left ventricle diastolic function. There’s a strong correlation between FGF23 with left ventricle diastolic function in patients with CKD.